2018
DOI: 10.1021/acschemneuro.7b00495
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship Studies of a Macrocyclic AGRP-Mimetic Scaffold c[Pro-Arg-Phe-Phe-Asn-Ala-Phe-DPro] Yield Potent and Selective Melanocortin-4 Receptor Antagonists and Melanocortin-5 Receptor Inverse Agonists That Increase Food Intake in Mice

Abstract: The melanocortin system has five receptors, and antagonists of the central melanocortin receptors (MC3R, MC4R) are postulated to be viable therapeutics for disorders of negative energy balance such as anorexia, cachexia, and failure to thrive. Agouti-related protein (AGRP) is an antagonist of the MC3R and an antagonist/inverse agonist of the MC4R. Biophysical NMR-based structural studies have demonstrated that the active sequence of this hormone, Arg-Phe-Phe, is located on an exposed β-hairpin loop. It has pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(53 citation statements)
references
References 74 publications
4
49
0
Order By: Relevance
“…However, Schild analysis of antagonist potency has indicated that AGRP(109–118) possesses submicromolar antagonist potency at the MC4R 46 47 . Many subsequent studies have observed similar melanocortin receptor pharmacology, including agonist activity at the mMC1R, micromolar potency at the mMC3R, and a range of potencies at the mMC4R (generally ranging from micromolar to nanomolar) 41 43 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Schild analysis of antagonist potency has indicated that AGRP(109–118) possesses submicromolar antagonist potency at the MC4R 46 47 . Many subsequent studies have observed similar melanocortin receptor pharmacology, including agonist activity at the mMC1R, micromolar potency at the mMC3R, and a range of potencies at the mMC4R (generally ranging from micromolar to nanomolar) 41 43 …”
Section: Introductionmentioning
confidence: 99%
“…Although peptide 1 possessed increased potency compared to the disulfide cyclized peptide at the mMC4R, it still does not match the potency of the native hormone AGRP (pA 2 = 8.7–9.1) 42 . Therefore, the SAR around this octapeptide scaffold has been explored in order to generate more potent and/or selective MC4R antagonists 41 43 . These SAR analyses have been performed on the Phe 3 , Phe 4 , Asn 5 , Ala 6 , and Phe 7 positions.…”
Section: Introductionmentioning
confidence: 99%
“…41, 42 These macrocyclic ligands possessed >100-fold decreased antagonist potency at the MC3R compared to AGRP, micromolar agonist potency or higher at the MC1R, and select compounds were apparent inverse agonists at the MC5R. 4042…”
Section: Introductionmentioning
confidence: 99%
“…Distinct large-scale genome-wide association study analysis unveiled MC4R polymorphic gene variants associated with weight gain [12]. Pharmacological activators of MC4R are used to treat obese patients with MC4R genetic defects, and recently approved drugs for obesity (bupropion and naltrexone) activate the POMC system [13]. Conversely, MC4R antagonists or inverse agonists to treat anorexia cause increased food intake in animal models [13].…”
Section: Melanocortin System Function: Role In Weight Gain and Obesitymentioning
confidence: 99%